The impact of green human resource management (GHRM) on employee retention: Mediating role of job satisfaction / Adrian Assan Bell, Yen Ping Ki and Maggie May Jean Tang - Bell, Adrian Assan (Universiti Teknologi MARA Cawangan Sarawak, 2024)
This study examined how Green Human Resource Management (GHRM) influences job satisfaction and its subsequent impact on employee retention among working adults in Malaysia post-COVID-19. This research observed that employees with environmental awareness who actively contribute to environmental causes tend to find their work more meaningful. However, there is an existing research gap concerning the correlation between GHRM and job satisfaction, as only a limited number of studies have explored the potential impact of GHRM on individual-level outcomes like job satisfaction and retention. Data were collected from 153 employed adults aged between 18 and 60 in Malaysia through an online questionnaire administered via Microsoft Forms to address this gap. The study found that GHRM positively affects job satisfaction, and job satisfaction, in turn, positively influences employee retention among working adults in Malaysia post-COVID-19. Notably, this study found that job satisfaction mediates the association between GHRM and employee retention. This research offers valuable insights for practitioners regarding the direct and indirect connections among GHRM, job satisfaction, and employee retention within the specified context. Additionally, it contributes to the GHRM literature, particularly in the Malaysian context, by advocating for a segmentation approach in hypothesis development and supporting the use of job characteristics theory and Herzberg's Two-Factor Theory when determining the direct and indirect correlation between GHRM, job satisfaction, and employee retention.